2016
DOI: 10.1016/j.ajic.2016.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Potential effectiveness of copper surfaces in reducing health care–associated infection rates in a pediatric intensive and intermediate care unit: A nonrandomized controlled trial

Abstract: Exposure of pediatric patients to copper-surfaced objects in the closed environment of the intensive care unit resulted in decreased HAI rates when compared with noncopper exposure; however, the RRR was not statistically significant. The clinical effect size warrants further consideration of this intervention as a component of a systems-based approach to control HAIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 21 publications
4
60
0
Order By: Relevance
“…Indeed, in hospital-based studies, the majority of infections were bacterial, particularly methicillin-resistant Staphylococcus aureus, vancomycinresistant Enterococcus, or Clostridium difficile. 6,8,9 In our study, the outbreaks were of viral origin, and copper has also been shown to be efficacious against viruses. 20 A further strongpoint of our study is that it directly assessed HAIs, and not simply bacterial samples for culture.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Indeed, in hospital-based studies, the majority of infections were bacterial, particularly methicillin-resistant Staphylococcus aureus, vancomycinresistant Enterococcus, or Clostridium difficile. 6,8,9 In our study, the outbreaks were of viral origin, and copper has also been shown to be efficacious against viruses. 20 A further strongpoint of our study is that it directly assessed HAIs, and not simply bacterial samples for culture.…”
Section: Discussionsupporting
confidence: 49%
“…20 Few studies have investigated the efficacy of copper as a contact surface in reducing health careeassociated infections (HAIs) from a clinical point of view, and fewer were interventional studies. 6,8,9,11,12 A randomized, multicenter study in the intensive care unit by Salgado et al 6 showed that patients cared for in areas with copper alloy surfaces had a significantly lower risk of nosocomial infection. A quasiexperimental study by Von Dessauer et al 8 showed a numerical, although not statistically significant, reduction in HAIs in patients assigned to rooms with copper surfaces.…”
mentioning
confidence: 99%
“…Recent clinical trials showed that covering hightouch surfaces in hospital rooms with copper can significantly decrease the bacterial burden and can reduce the number of hospital-acquired infections by more than 50% (35,(45)(46)(47)(48). Because A. baumannii fomite-associated hospital outbreaks have been documented, specifically from a contaminated hospital bed and burn theater, evidence that copper effectively eliminates environmental A. baumannii is important (49).…”
Section: Figmentioning
confidence: 99%
“…The implementation of copper alloys on high-touch surfaces in the hospital resulted in decreased bacterial counts on surfaces in comparison with control surfaces. [18][19][20][21][22][23] Souli et al found copper coating reduced bacterial burden associated high-touch hospital items and lowered the number of surfaces contaminated with multidrug-resistant bacteria. 24 The ability of copper to lessen bacterial loads rapidly is important for continuously touched surfaces and therefore can more readily reduce the transmission of antibioticresistant bacteria.…”
mentioning
confidence: 99%